Upregulation of MTA1 in Colon Cancer Drives A CD8+ T Cell-Rich But Classical Macrophage-Lacking Immunosuppressive Tumor Microenvironment - Zhou, Yantong; Nan, Peng; Li, Chunxiao; Mo, Hongnan; Zhang, Ying; Wang, Haijuan; Xu, Dongkui; Ma, Fei; Qian, Haili (Frontiers in Oncology, 2022)
Background:The MTA1 protein encoded by Metastasis-Associated Protein 1 (MTA1) is a key component of the ATP-dependent nucleosome remodeling and deacetylase (NuRD) complex which is widely upregulated in cancers. MTA1 extensively affects downstream genes expression by participating in chromatin remodeling. Though it was defined as a metastasis-associated gene from the first reports and metastasis is a process prominently affected by tumor microenvironment, whether it affects the microenvironment has not been investigated. In our study, we elucidate the regulatory effect of MTA1 on tumor-associated macrophages (TAMs) and how this regulation affects the anti-tumor effect of cytotoxic T lymphocyte (CTL) in tumor microenvironment of colorectal cancer. Methods:We detected the cytokines affected by MTA1 expression via cytokine antibody array in control HCT116 cells and HCT116 cells overexpressing MTA1. Multiplex IHC staining was conducted on colorectal cancer tissue array from our cancer cohort. Flow cytometry (FCM) was performed to explore the polarization of macrophages in co-culture system and anti-tumor killing effect of CTL in co-culture system. Bioinformatics analysis was conducted to analyze the Cancer Genome Atlas (TCGA) colorectal cancer cohort and single cell RNA-seq data, aiming to assess the immune infiltration status of the TCGA colorectal cancer cohort and functions of myeloid cells. Results:The upregulated MTA1 in colorectal cancer drove an immunosuppressive tumor microenvironment. In the tumor microenvironment of MTA1-upregulated colorectal cancer, though CD8+T cells were significantly enriched, macrophages were significantly absent, which impaired the CTL effect of CD8+ T cells on tumor cells. More than that, upregulated MTA1 in tumor cells significantly induced infiltrated macrophages into tumor-associated macrophage phenotypes and further weakened the cytotoxic effect of CD8+T cells. Conclusion:Upregulation of MTA1 in colorectal cancer drives an immunosuppressive tumor microenvironment by decreasing the microphages from the tumor and inducing the residual macrophages into tumor-associated microphage phenotypes to block the activation of the killing CTL, which contributes to cancer progression.